Comparison of family members' and nurses' satisfaction with the care in intensive care units at Hospital Universiti Sains Malaysia - Che Mood@Mahyiddin, Nur Syakilah (2015)
Introduction: Family members’ satisfaction is an important measurement in determining the quality of care of patients in the critical care area. Objective: The purpose of this descriptive research was to examine the difference in satisfaction between family members and nurses in Intensive Care Unit, Hospital Universiti Sains Malaysia (Hospital USM). Methods: Data were collected from convenience sample of 64 family members and 76 intensive care nurses using self-administered questionnaires from January 2013 until June 2013. The study took place in three places: medical intensive care unit (MICU), surgical intensive care unit (SICU) and Neurological ICU (NeuroICU). Validated Malay version of Critical Care Family Satisfaction Survey (CCFSS) was used. The reliability of the questionnaire was tested by researcher and analysed using Statistical Package for Social Science (SPSS). The Cronbach’s alpha of the questionnaire was 0.91 and 0.80-0.87 for each domain. Results: The mean for the satisfaction scores of family members and nurses were 20.92 (SD = 3.22) and 22.02 (SD = 2.38) respectively. This indicates that the families and nurses were generally satisfied towards the care provided. However, the family members of critically ill patients and critical care nurses had significance differences in important of satisfaction (p < 0.05). In addition, there was also had significance difference in satisfaction domains which were information and support (p < 0.05). This differences shows the families and nurses have different view of satisfaction towards care. The family members more concern about the proximity, followed by comfort, support information and assurance. It is because family members were satisfied with care when they can visit the patient frequently and always near to the patient, to be informed of patient’s treatment progress and privacy was given during visiting hours. Nevertheless, the nurses rate the important of satisfaction domain in a different way. The nurses believe that the important of satisfaction domains in providing care were support, followed by information, comfort, proximity and assurance. The nurses agreed that the support was the most important component in providing care because support and encouragement would reduce family members’ stress and will help them to cope with the critical care situation. The waiting time duration and health related occupation background of family members were the predictor of family members satisfaction with care (p = 0.010) and (p = 0.006) respectively (R2 = 0.22). The family members waiting time duration and health related occupation background were also the predictor factors influenced the satisfaction domain: assurance, information and support (p < 0.05) with R2 = 0.16, R2 = 0.27 and R2 = 0.27 respectively. Conclusion: These findings indicate that the family members and nurses were satisfied with the care provided in the critical care unit and it contributes to the improvement of unmet interventions by the nurses during care delivery.